Population based epidemiology of amyotrophic lateral sclerosis using capture–recapture methodology. Issue 10 (27th May 2011) - Huisman, Mark H B; de Jong, Sonja W; van Doormaal, Perry T C; Weinreich, Stephanie S; Schelhaas, H Jurgen; van der Kooi, Anneke J; de Visser, Marianne; Veldink, Jan H; van den Berg, Leonard H
Abstract : Background: Variation in the incidence rate in epidemiological studies on amyotrophic lateral sclerosis (ALS) may be due to a small population size and under ascertainment of patients. The previously reported incidence decline in the elderly and a decrease in the male:female ratio in postmenopausal age groups have yet to be confirmed. Methods: ALS epidemiology in a large population based register in The Netherlands was studied between 1 January 2006 and 31 December 2009, and applied capture–recapture methodology in separate age and gender groups to adjust for the number of unobserved patients. Results: 1217 incident patients were observed, and a capture–recapture incidence of 2.77 per 100 000 person-years (95% CI 2.63 to 2.91). Prevalence on 31 December 2008 was 10.32 per 100 000 individuals (95% CI 9.78 to 10.86). The incident cohort had a higher median age at onset (63.0 vs 58.1 years) and more bulbar onset patients (30.0% vs 19.1%) compared with the prevalent cohort. Incidence and prevalence peaked in the 70–74 year age group followed by a rapid decline in older age. The male:female ratio in the premenopausal age group (1.91, 95% CI 1.32 to 2.79) was not significantly higher than that in the postmenopausal age group (1.50, 95% CI 1.34 to 1.67). Conclusion: The marked difference in patient characteristics between incident and prevalent cohorts underscores the importance of including incident patients when studying susceptibility or disease modifying factors in ALS. The incidence decline in the elderly may suggest that ALS is not merely the result of ageing. Absence of a significant postmenopausal drop in the male:female ratio suggests that the protective role of female sex hormones in ALS is limited.